Indonesian Language Accuracy Issues on Television - Hermandra, Hermandra; Diah, Fangiana Safitri; Zulhafizh, Zulhafizh (Proceedings of the UR International Conference on Educational Sciences, 2018)
Television influences the use and understanding of Indonesian language. Disobedience and ignorance of rules of the language bring a negative impact for the language itself. Such condition encourages the writer to carry out a study on the implementation of Indonesian language rules on television. This study aims to find out language issues on televisions. The method used in the study is documentation. The approach used is the video or photo recording approach. The findings of the data analysis reveal that some mistakes regarding the language rules are found on the media. The mistakes deal with academic title writing, capitalization, the sequence of letters, misspelling, vocabulary, and cohesions. These mistakes can bring negative impact to viewers. Viewers may believe everything presented on television is in accordance with provisions of Indonesian language rules.Therefore, journalists are required to be careful in presenting a program on television.